Kidney effects in long term exposed lead smelter workers. Issue 3 (March 1992) - Gerhardsson, L; Chettle, D R; Englyst, V; Nordberg, G F; Nyhlin, H; Scott, M C; Todd, A C; Vesterberg, O
Abstract : Occupational exposure to lead may cause kidney damage. This study was carried out on a cohort of 70 active and 30 retired long term exposed lead smelter workers. Their kidney function was compared with 31 active and 10 retired truck assembly workers who had no occupational exposure to lead. The lead workers had been regularly followed up with measurements of lead concentration in blood since 1950. Previous exposure to lead was calculated as a time integrated blood lead index for each worker. Blood and urine samples were obtained from all subjects. The concentration of lead in blood (B-Pb) and urine (U-Pb) was analysed. The urinary concentrations of several sensitive indicators of early tubular (U-beta 2-microglobulin (U-beta 2-m); U-N-acetyl-beta-glucosaminidase (U-NAG)) and glomerular kidney damage (U-albumin) were determined. The B-Pb and U-Pb values were significantly higher among active and retired lead workers compared with their corresponding control groups. The highest concentrations were found among the active lead workers. The concentrations of the parameters of kidney function investigated were of the same magnitude for exposed workers and controls. No clinical signs of renal impairment were found among the workers. No correlations of clinical importance existed between concentrations of U-albumin, U-beta 2-m, and U-NAG activity on the one hand and the concentrations of B-Pb, cumulative blood lead index, U-Pb, and lead concentrations in the calcaneus and tibia on the other, among lead workers and controls. Despite many years of moderate to heavy exposure to lead, particularly for the retired lead workers, no signs of adverse effects on the kidney such as early tubular or glomerular malfunction were found. Reversible changes in kidney function during the 1950s and 1960s could not be excluded, however, due to a greater exposure to lead during that time.